Neurofilaments in spinocerebellar ataxia type 3: blood biomarkers at the preataxic and ataxic stage in humans and mice. Issue 7 (8th June 2020) - Wilke, Carlo; Haas, Eva; Reetz, Kathrin; Faber, Jennifer; Garcia‐Moreno, Hector; Santana, Magda M; van de Warrenburg, Bart; Hengel, Holger; Lima, Manuela; Filla, Alessandro; Durr, Alexandra; Melegh, Bela; et al.
Abstract: With molecular treatments coming into reach for spinocerebellar ataxia type 3 (SCA3), easily accessible, cross‐species validated biomarkers for human and preclinical trials are warranted, particularly for the preataxic disease stage. We assessed serum levels of neurofilament light (NfL) and phosphorylated neurofilament heavy (pNfH) in ataxic and preataxic subjects of two independent multicentric SCA3 cohorts and in a SCA3 knock‐in mouse model. Ataxic SCA3 subjects showed increased levels of both NfL and pNfH. In preataxic subjects, NfL levels increased with proximity to the individual expected onset of ataxia, with significant NfL elevations already 7.5 years before onset. Cross‐sectional NfL levels correlated with both disease severity and longitudinal disease progression. Blood NfL and pNfH increases in human SCA3 were each paralleled by similar changes in SCA3 knock‐in mice, here also starting already at the presymptomatic stage, closely following ataxin‐3 aggregation and preceding Purkinje cell loss in the brain. Blood neurofilaments, particularly NfL, might thus provide easily accessible, cross‐species validated biomarkers in both ataxic and preataxic SCA3, associated with earliest neuropathological changes, and serve as progression, proximity‐to‐onset and, potentially, treatment‐response markers in both human and preclinical SCA3 trials. Synopsis: This cross‐species study establishes neurofilament blood levels (NfL/pNfH) as biomarkers of neuronal damage in spinocerebellar ataxia type 3 (SCA3) in humans and mice, both at the manifest and premanifest disease stage. NfL levels capture proximity to symptom onset and disease progression. Blood levels of neurofilament light (NfL) and phosphorylated neurofilament heavy (pNfH) were assessed in manifest and premanifest subjects of two multicentric SCA3 cohorts and in SCA3 knock‐in mice. NfL and pNfH levels were increased at the manifest disease stage, with NfL levels reflecting both clinical disease severity and disease progression. NfL elevations in the premanifest stage were present already 7.5 years before the individual expected onset, with levels increasing further in temporal proximity to symptom onset. NfL and pNfH increases in the SCA3 mouse model started also already at the premanifest stage, closely following ataxin‐3 aggregation and even preceding Purkinje cell loss in the brain. Abstract : This cross‐species study establishes neurofilament blood levels (NfL/pNfH) as biomarkers of neuronal damage in spinocerebellar ataxia type 3 (SCA3) in humans and mice, both at the manifest and premanifest disease stage. NfL levels capture proximity to symptom onset and disease progression.